The Reality of the Dimensions of Organizational Memory : A Survey Study of the Opinions of a Sample of Employees in the Vocational Education Department / Nineveh Education Directorate - Altaie, Nabaa M. (PROSPECTIVE RESEARCHES, 2025)
The research aims to explore the reality of the dimensions of organizational memory, represented by administrative memory, cultural memory, and technological memory, and to address the challenges faced by the Vocational Education Department. The main question posed is: What is the level of availability of organizational memory dimensions in the studied organization according to the perceptions of the research sample? The research population consisted of 68 employees in the Vocational Education Department. To achieve the research objectives, a questionnaire was used for data collection. A total of 68 forms were distributed, and 63 valid responses were analyzed. The research adopted a descriptive-analytical methodology and utilized various statistical methods, including frequencies, percentages, means, and standard deviations, using SPSS V26 software. Based on the description and diagnosis of the research dimensions, the study tested the influence relationships among these dimensions according to the research's hypothetical framework. The key findings revealed no significant variation among the dimensions of organizational memory in the Vocational Education Department. Among the most important recommendations, the research emphasized the necessity of focusing on the dimensions of organizational memory within the Vocational Education Department. The findings highlighted the variation in these dimensions. Therefore, if the organization aims to achieve excellence and innovation in its performance and fully benefit from organizational memory for all stakeholders, it must develop programs and policies that prioritize fostering creativity in organizational memory and implementing its principles.